Σχεδιασμός και τεχνοοικονομική μελέτη μονάδας ανακύκλωσης χαρτιού για την επαρχία της Λεμεσού - Νικολάου, Παύλος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Preservation of the environment and implementing policies that promote recycling and re-use of materials is more imperative than ever before, bearing in mind the magnitude of the ecological disaster caused by human economic activity and the exploitation of the natural environment. An organization like Cyprus University of Technology (TEPAK) uses and sends for recycling tons of waste paper every year. The collection and recycling of waste paper at this stage does not burden economically the institution as it is collected free of charge by a recycling company. Considering the possibility that the institution creates an autonomous paper recycling plant, the purpose of this dissertation, initially was the design of a small paper recycling facility that exploits the institution's waste and the techno-economic study of the potential profit that could obtain the University through such a private venture. After measuring the weight of the paper waste coming from the institution alongside with studying the available machinery' in the market place, we came to the conclusion that the market does not dispose of recycling machines for such small quantities of paper. So, we turned our attention to the measured amounts of recycling waste paper in Limassol district. The present techno-economic study is based on these recorded figures as these are provided by the recycling company. In the context of this study, we received offers from international companies dealing with paper recycling. The results indicate that a recycling plant/unit that would exploit paper waste only from Limassol District for the production of paper rolls weighing 60 to 80 grams per square meter would not be viable. Finally, a comparison was made for the exploitation of paper waste collected on a pan-Cyprian basis with an aim to produce paper rolls weighing between 115 and 200 grams per square meter. The resulting are more encouraging for this scenario.
Keywords: Paper recycling; Techno-economic study; Environment; Ανακύκλωση χαρτιού; Τεχνοοικονομική μελέτη; Περιβάλλον